Implications of perceived empowering motivational climate on athletes` goal-regulatory processes: A longitudinal analysis - Martínez-González, N.; Atienza, F. L.; Balaguer, I. (Journal of Sports Sciences, 2026)
This study explores how athletes` perceptions of empowering climates can influence athletes` goal regulatory processes over the competitive season. The purpose of this research was to test, using a longitudinal design, the relationship between athletes` perceptions of an empowering climate, goal motives, and goal-directed effort. A total of 112 university athletes (M = 20.90; SD = 2.79) completed a multi-section questionnaire at two time points during the season. Changes in perceptions of an empowering motivational climate positively predicted changes in autonomous goal motives (but not controlled ones), which in turn led to positive changes in goal-directed effort. These results suggest that athletes who perceive a climate of empowerment on the part of their coach tend to pursue goals autonomously, leading to greater effort directed towards those goals. Overall, the findings provide information on the implications of athletes` perception of the empowering climates created by their coaches for the autonomous motivation underlying their goals, as well as for enhancing their effort sustainability and facilitating their goal attainment in high-level sporting contexts. In addition, the study supports the positive implications of perceived empowering climates in relation to athletes` pursuit of adaptive goals when examined over time.